1997
DOI: 10.1007/s002469900145
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Three-Dimensional Echocardiographic Reconstruction of Congenital Cardiac Septation Defects

Abstract: Dynamic three-dimensional echocardiographic reconstructions of 27 cardiac septation defects were performed in 19 sedated infants and children. Using a subxiphoid rotational scanning approach, complete visualization of the entire shape and breadth of the defect was attained in 11 of 16 ventricular septal defects and 9 of 11 atrial septal defects. This technique enabled the operator to cut slices from the three-dimensional block of echocardiographic data in order to present septation defects in a region- or lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Tantengco et al [ 24 ] showed that 3DE provided unique en face views of atrial and ventricular septal defects. Cheng et al [ 25 ] studied 38 patients with atrial and/or ventricular septal defects using 3DE, and compared their results with 2DE and surgical fi ndings.…”
Section: Atrial and Ventricular Septamentioning
confidence: 99%
“…Tantengco et al [ 24 ] showed that 3DE provided unique en face views of atrial and ventricular septal defects. Cheng et al [ 25 ] studied 38 patients with atrial and/or ventricular septal defects using 3DE, and compared their results with 2DE and surgical fi ndings.…”
Section: Atrial and Ventricular Septamentioning
confidence: 99%
“…[26] Cheng et al , studied 38 patients with atrial and / or ventricular septal defects using 3DE, and compared their results to 2DE and surgical findings. They demonstrated novel 3DE views of both atrial and ventricular septal defects and improved accuracy of quantification of the size of the defect by 3DE compared to 2DE (r = 0.92 vs. r = 0.69).…”
Section: De Technologymentioning
confidence: 99%
“…6,9 However, this imaging plane also has been used successfully for three-dimensional studies in older adolescents and adults. 6,9 However, this imaging plane also has been used successfully for three-dimensional studies in older adolescents and adults.…”
Section: Acquisition Phasementioning
confidence: 99%